Life behind leaves: capability, poverty and social vulnerability of tea garden workers in Bangladesh. (3rd September 2019) - Islam, Md Nazrul; Al-Amin, Md
ABSTRACT: This article aims to investigate the causes of poverty and vulnerability, and the survival strategies, of the tea garden workers in Bangladesh. The study was conducted drawing insights from Sen's and Nussbaum's capability approach and employing a triangulation of methods, which include intensive interviews, focus group discussions, and key informant interviews, for collecting data. The study finds that capability deprivation in various spheres of life remains the most important cause of poverty and vulnerability among the tea garden workers. The paper offers some pragmatic policy recommendations to reduce the workers' poverty and vulnerability.